Telaah Tematik Esensi Makna ‘Ismah dalam al-Qur’an - Suraya Attamimi; Aswadi Aswadi; Hammis Syafaq (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Thematic Study of the Essence of the Meaning of ‘Ismah in the Qur'anThis article discusses the interpretation of the term ‘ismah in the Qur'an. As a word with conceptual implications, ‘ismah is often used by Muslim scholars when discussing the incorruptible innocence of the prophets from sins (‘ismat al-Anbiya>’). This article reviews the meaning of the word along with its scope to see the appropriateness of the theological connotations by collecting all Qur’anic verses that use the word ‘ismah and its derivations. The twelve verses collected were then arranged chronologically according to the moments of their revelation and analyzed using a thematic interpretation method. The results of this study indicate that ‘ismah carries two meanings: to prevent or to protect (man‘) and to be steadfast (imsa>k and mula>zamah). Therefore, ‘ismah has the same meaning as taqwa>, hifz, and isti‘a>dzah. The association of ‘ismah as a theological concept in the doctrine of prophethood, as commonly discoursed by the mufassirs, is the highest achievement. Meanwhile, the use of this term in the Qur'an shows that ‘ismah is correlated with three other terms, namely rahmah, fadl, and huda>, which focus more on the process of achieving ‘ismah in the theological context. This article concludes that the ‘ismah of the prophets is the pinnacle of achievement of the human life process which requires vertical and horizontal faith and piety among human beings.